2017
DOI: 10.1002/bio.3320
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Studies on the luminescence properties of cerium co‐doping on Ca2MgSi2O7:Eu2+ phosphor by solid‐state reaction method

Abstract: Ca2MgSi2O7:Ce3+, Ca2MgSi2O7:Eu2+ and Ca2MgSi2O7:Eu2+,Ce3+ phosphors were prepared using the solid‐state reaction method. The crystal structures of the sintered phosphors were of melilite type, which has a tetragonal crystallography. The chemical compositions of the sintered phosphors was confirmed by energy dispersive X‐ray spectroscopy. The different thermoluminescence kinetic parameters [activation energy (E), frequency factor (s) and order of the kinetics (b)] of these phosphors were evaluated and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The decline in radius r yields a decreased crystal plane spacing d, which shifts the strongest diffraction peak in the high-angle direction. 9 . The Ca atoms are interspersed with these groups and are closely packed together to form a highly dense skeleton.…”
Section: Experimental Results and Discussion 21 Physical Phase Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in radius r yields a decreased crystal plane spacing d, which shifts the strongest diffraction peak in the high-angle direction. 9 . The Ca atoms are interspersed with these groups and are closely packed together to form a highly dense skeleton.…”
Section: Experimental Results and Discussion 21 Physical Phase Characterizationmentioning
confidence: 99%
“…In addition, Si and O are connected to form form SiO 4 tetrahedra, Mg and O are connected to form MgO 4 tetrahedra, and the two tetrahedra are connected by sharing an O atom to form the (Si/Mg) O 7 group (Fig. (2c)); The average M-O distances are 1.916 Å (M=Mg) and 1.624 Å (M=Si), on average9 . The Ca atoms are interspersed with these groups and are closely packed together to form a highly dense skeleton.…”
mentioning
confidence: 99%
“…1c; it has a tetragonal melilite-type and non-centrosymmetric crystal structure. 39,40 There are two sites of Ca 2+ , which are sixcoordinated and eight-coordinated, respectively. 41 Comparison of the ionic radii of Ca 2+ (CN 6 = 1.00 Å, CN 8 = 1.12 Å), Mg 2+ (CN 6 = 0.72 Å, CN 8 = 0.89 Å), Si 2+ (CN 4 = 0.26 Å, CN 6 = 0.40 Å) and Eu 2+ (CN 6 = 1.17 Å, CN 8 = 1.25 Å) suggested that Eu 2+ should occupy the lattice position of Ca 2+ .…”
Section: Structural Analysesmentioning
confidence: 99%
“…Theoretically, we can synthesize persistent luminescence materials emitting any color by adjusting the chemical components. The most widely used and studied matrixes include silicates [9], gallium oxides [10], gallogermanates [11], aluminates [12] and so on [13][14][15][16]. Among them, CaAl 2 O 4 :Eu 2+ , Nd 3+ and SrAl 2 O 4 :Eu 2+ , Dy 3+ with overwhelming strong and long-lasting PL have been commercialized and widely used in various fields [2,17] [18][19][20].…”
Section: Introductionmentioning
confidence: 99%